Microstrip Diplexers with double-stub bandpass filters - Khalaj-Amirhosseini, M.; Moghavvemi, M.; Ameri Mahabadi, H.; Attaran, A. (2011)
This paper presents a microstrip diplexer using two Double-Stub Band-Pass Filters (DS-BPFs), composed of several double-stubs connected to a main microstrip line. Each DS-BPF has a null at the center frequency of the other. Therefore, these types of filters are suitable for diplexers with two near frequencies. A diplexer at frequencies 5.875 and 6.225 GHz is designed, fabricated and measured. Measured results of the fabricated diplexer have a good agreement with the calculated results.